ANALYSIS OF NURSING CARE FOR DIVERTICULITIS PATIENTS USING PROGRESSIVE MUSCLE RELAXATION THERAPY TO OVERCOME ANXIETY AT DARMO HOSPITAL SURABAYA - Agustin, Dian Rahmawati; Putri, Rahmadaniar Aditya; Soleha, Umdatus; Setiawan, M. Arif Helmi (Nurse and Holistic Care, 2024)
Introduction: Diverticulitis is a disease caused by an unhealthy lifestyle, lack of dietary fiber intake and a high-fat diet as well as a lack of physical activity are the main triggers for this disease. In diverticulitis sufferers, anxiety problems often arise due to concerns about their health condition in the future and what their health status will be if surgery is performed. Objective: This study aims to determine the description of nursing care and analyze the application of progressive muscle relaxation therapy in diverticulitis patients with anxiety problems. Methods: This research uses a case study method by providing nursing care through a nursing process approach. The research was conducted at Darmo Hospital Surabaya on 23-25 September 2022 by applying progressive muscle relaxation therapy to 1 respondent for 3 days with an intensity of 2x/day with a duration of 15-20 minutes, evaluating the patient using the Hamilton Rating Scale for Anxiety instrument (HARS). Results: The results of this case study show a decrease in the level of anxiety felt by the patient after being given progressive muscle relaxation therapy. The level of anxiety decreased from moderate anxiety (score 22) to mild anxiety (score 14), the patient appeared calm and relaxed, and the patient's pulse decreased. This research concludes that the application of progressive muscle relaxation therapy can be an alternative to reduce anxiety in diverticulitis patients. Conclusions: However, the findings should be interpreted with cautiously due to the study's reliance on a single case and the short intervention period. Future research should explore the long-term effects of progressive muscle relaxation therapy on a larger and more diverse patient population.